Oxytocin and Social Sensitivity: Gene Polymorphisms in Relation to Depressive Symptoms and Suicidal Ideation - McQuaid, Robyn J.; McInnis, Opal A.; Matheson, Kimberly; Anisman, Hymie (Frontiers in Human Neuroscience, 2016)
Although the neuropeptide oxytocin has been associated with enhanced prosocial behaviors, it has also been linked to aggression and mental health disorders. Thus, it was suggested that oxytocin might act by increasing the salience of social stimuli, irrespective of whether these are positive or negative, thus increasing vulnerability to negative mental health outcomes. The current study (N = 243), conducted among White university students, examined the relation of trauma, depressive symptoms including suicidal ideation in relation to a single nucleotide polymorphism (SNP) within the oxytocin receptor gene (OXTR), rs53576, and a SNP on the CD38 gene that controls oxytocin release, rs3796863. Individuals with the polymorphism on both alleles (AA genotype) of the CD38 SNP had previously been linked to elevated plasma oxytocin levels. Consistent with the social sensitivity perspective, however, in the current study, individuals carrying the AA genotype displayed elevated feelings of alienation from parents and peers as well as increased levels of suicidal ideation. Moreover, they tended to report elevated depressive symptoms compared to CC homozygotes. It was also observed that the CD38 genotype moderated the relation between trauma and suicidal ideation scores, such that high levels of trauma were associated with elevated suicidal ideation among all CD38 genotypes, but this relationship was stronger among individuals with the AA genotype. In contrast, there was no relationship between the OXTR SNP, rs53576, depression or suicidal ideation. These findings support a social sensitivity hypothesis of oxytocin, wherein the AA genotype of the CD38 SNP, which has been considered the ‘protective allele’ was associated with increased sensitivity and susceptibility to disturbed social relations and suicidal ideation.